Cardiovascular health in perspective: a comprehensive five-year geodatabase of hospitalizations and environmental factors in Mashhad, Iran - Shahab MohammadEbrahimi; Mohammad Dehghan; Behzad Kiani (BMC Research Notes)
Abstract Objectives This data note presents a comprehensive geodatabase of cardiovascular disease (CVD) hospitalizations in Mashhad, Iran, alongside key environmental factors such as air pollutants, built environment indicators, green spaces, and urban density. Using a spatiotemporal dataset of over 52,000 hospitalized CVD patients collected over five years, the study supports approaches like advanced spatiotemporal modeling, artificial intelligence, and machine learning to predict high-risk CVD areas and guide public health interventions. Data description This dataset includes detailed epidemiologic and geospatial information on CVD hospitalizations in Mashhad, Iran, from January 1, 2016, to December 31, 2020. It contains 52,176 confirmed CVD cases and includes demographic information such as age, gender, admission date, ICD-10 codes, occurrence of death, and length of hospital stay. The median age of patients was 64 years, with 54.44% male. A notable 9.41% of patients died during hospitalization. In addition to the CVD hospitalization case file and its shape file created by joining with 1301 census tracts, this dataset includes environmental factors such as air quality indicators (SO2, PM2.5, CO, etc.). It also incorporates socio-economic variables (population density, illiteracy, and unemployment rates), public infrastructure, and built environment data, providing a comprehensive view of cardiovascular health in Mashhad.